Identification and Expression Analysis of Wheat TaGF14 Genes - Guo, Jun; Dai, Shuang; Li, Haosheng; Liu, Aifeng; Liu, Cheng; Cheng, Dungong; Cao, Xinyou; Chu, Xiusheng; Zhai, Shengnan; Liu, Jianjun; Zhao, Zhendong; Song, Jianmin (Frontiers in Genetics, 2018)
The 14-3-3 gene family members play key roles in various cellular processes. However, little is known about the numbers and roles of 14-3-3 genes in wheat. The aims of this study were to identify TaGF14 numbers in wheat by searching its whole genome through blast, to study the phylogenetic relationships with other plant species and to discuss the functions of TaGF14s. The results showed that common wheat harbored 20 TaGF14 genes, located on wheat chromosome groups 2, 3, 4 and 7. Out of them, eighteen TaGF14s are non-ε proteins, and two wheat TaGF14 genes, TaGF14i and TaGF14f, are ε proteins. Phylogenetic analysis indicated that these genes were divided into six clusters: cluster 1 (TaGF14d, TaGF14g, TaGF14j, TaGF14h, TaGF14c and TaGF14n); cluster 2 (TaGF14k); cluster 3 (TaGF14b, TaGF14l, TaGF14m and TaGF14s); cluster 4 (TaGF14a, TaGF14e and TaGF14r); cluster 5 (TaGF14i and TaGF14f); and cluster 6 (TaGF14o, TaGF14p, TaGF14q and TaGF14t). Tissue-specific gene expressions suggested that all TaGF14s were likely constitutively expressed, except two genes, i.e., TaGF14p and TaGF14f. And the highest amount of TaGF14 transcripts were observed in developing grains at 20 days post anthesis (DPA), especially for TaGF14j and TaGF14l. After drought stress, five genes, i.e., TaGF14c, TaGF14d, TaGF14g, TaGF14h and TaGF14j, were up-regulated expression under drought stress for both 1 h and 6 h, suggesting these genes played vital role in combating against drought stress. However, all the TaGF14s were down-regulated expression under heat stress for both 1 h and 6 h, indicating TaGF14s may be negatively associated with heat stress by reducing the expression to combat heat stress or through other pathways. These results suggested that cluster 1, e.g., TaGF14j, may participate in the whole wheat developing stages, e.g., grain-filling (starch biosynthesis) and may also participate in combating against drought stress. Subsequently, a homologue of TaGF14j, TaGF14-JM22, were cloned by RACE and used to validate its function. Immunoblotting results showed that TaGF14-JM22 protein, closely related to TaGF14d, TaGF14g and TaGF14j, can interact with AGP-L, SSI, SSII, SBEIIa, and SBEIIb in developing grains, suggesting that TaGF14s located on group 4 may be involved in starch biosynthesis. Therefore, it is